2009
DOI: 10.1007/s11218-009-9098-y
|View full text |Cite
|
Sign up to set email alerts
|

The Peer Interaction in Primary School Questionnaire: testing for measurement equivalence and latent mean differences in bullying between gender in Egypt, Saudi Arabia and the USA

Abstract: The Peer Interaction in Primary School Questionnaire (PIPSQ) was developed to assess individuals' levels of bullying and victimization. This study used the approach of latent means analysis (LMA) within the framework of structural equation modeling (SEM) to explore the factor structure and gender differences associated with the PIPSQ in a sample of Egyptian (N = 361), Saudi Arabian (N = 350) and USA (270) children. Results of the confirmatory factor analysis are consistent with previous work and support the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 43 publications
3
25
2
3
Order By: Relevance
“…The latter group indicated a greater likelihood of helping victims than the former group. These results are in line with some more recent findings according to which Egyptian and Saudi Arabian participants (taken as representing collectivistic cultures) revealed a higher level of bullying behavior than Americans (Hussein, 2009). These findings are explained by means of the stronger need of collectivists to belong to a group, to be accepted by the ingroup and to have a social identity that coheres to that of the larger affiliation group.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The latter group indicated a greater likelihood of helping victims than the former group. These results are in line with some more recent findings according to which Egyptian and Saudi Arabian participants (taken as representing collectivistic cultures) revealed a higher level of bullying behavior than Americans (Hussein, 2009). These findings are explained by means of the stronger need of collectivists to belong to a group, to be accepted by the ingroup and to have a social identity that coheres to that of the larger affiliation group.…”
supporting
confidence: 92%
“…Therefore, members of the ingroup behave in a way that fosters conformity to group norms, and the bias in favor of the ingroup versus the outgroup. Moreover, according to Hussein (2009), the observed higher levels of bullying in collectivistic cultures result from the authoritarian parenting style that is widely used in such cultures.…”
mentioning
confidence: 99%
“…For example, studies have shown a greater likelihood of bullying incidents in collectivistic cultures [68]. Similarly, Hussein provided additional supportive evidence that individuals in collectivistic cultures may be more disposed to experiences of bullying [69]. This may come as a result of the authoritarian parenting, which is more evident in collectivistic cultures and strongly associated with the involvement in bullying.…”
Section: Parental Values and Child Externalizing Problemsmentioning
confidence: 92%
“…Bullying remains prevalent within schools throughout the world (Bibou-Nakou et al 2012; Hussein 2010; Rigby and Smith 2011), where it poses a threat to the health of students internationally. Bullying is characterized by aggressive behavior that is intentionally harmful, occurs repeatedly, and involves an imbalance of physical or psychological power between victim and perpetrator (Olweus 1993).…”
Section: Introductionmentioning
confidence: 99%
“…That is, protective factors buffer victims of bullying by lessening the impact of bullying on negative outcomes. Although some research has focused on factors that reduce adolescents’ likelihood of experiencing bullying (e.g., Baldry and Farrington 2005; Wang et al 2009), we focus on protective factors that enhance resilience to the ongoing experiences of bullying, given that bullying persists in the United States (Nansel 2001; Wang et al 2009) and elsewhere in the world (Bibou-Nakou et al 2012; Hussein 2010; Rigby and Smith 2011) despite efforts to end it (Fekkes 2004; Olweus 1996). Other people serve as significant protective factors for adolescents experiencing bullying.…”
Section: Introductionmentioning
confidence: 99%